A novel BRCA2 splice variant identified in a young woman. Issue 12 (7th November 2020) - Nicolussi, Arianna; Belardinilli, Francesca; Ottini, Laura; Petroni, Marialaura; Capalbo, Carlo; Giannini, Giuseppe; Coppa, Anna
Abstract: Background: BRCA1 / 2 VUSs represent an important clinical issue in risk assessment for the breast/ovarian cancer families (HBOC) families. Among them, some occurring within the intron‐exon boundary may lead to aberrant splicing process by altering or creating de novo splicing regulatory elements or unmasking cryptic splice site. Defining the impact of these potential splice variants at functional level is important to establish their pathogenic role. Methods: Genomic DNA was extracted from peripheral blood sample of a young woman affected with breast cancer belonging to a HBOC family and the entire coding regions of the BRCA1 and BRCA2 genes were amplified using the Ion AmpliSeq BRCA1 and BRCA2 Panel. The BRCA2 c.682‐2delA variant has been characterized by RT‐PCR analysis performed on mRNA extracted from blood and lymphoblastoid cell line. Results: We demonstrated that a novel BRCA2 c.682‐2delA variant at the highly conserved splice consensus site in intron 8 disrupts the canonical splice acceptor site generating a truncated protein as predicted by several bioinformatics tools. Segregations analysis in the family and LOH performed on proband breast cancer tissue further confirmed its classification as pathogenic variant. Conclusion: Combining different methodologies, we characterized this new BRCA2 variant and provided findings of clinical utility for its classification as pathogenic variant. Abstract : In this work, we described a novel BRCA2 splice variant identified in a 33‐year‐old breast cancer patient belonging to a HBOC family. Our approach, which combines different methodologies, has been able to characterize this new BRCA2 variant and provide findings of clinical utility for its classification as pathogenic variant.